Diazotizable supports of potential interest as affinity chromatography matrices - Benes, M J; Lenfeld, J; Prádová, O (Journal of molecular recognition, 1996)
Immobilization of affinity ligands, proteins, enzymes and other functional groups by azo coupling is based on the high reactivity of the support-carrying diazonium groups towards both low- and high-molecular weight compounds containing certain groupings such as phenols, imidazole and some other heterocycles, thiols and amines. The precursor of diazonium group is a diazotizable amine on the matrix. Remarkable progress in its preparation was achieved by application of (4-amino-phenyl)-(2-sulphatoxyethyl) sulphone-type reagents for functionalization of the matrix. A similar type of amine precursor is prepared by the reaction of monosubstituted sulphanilamide with epoxide-containing matrix. The presence of a SO2 group in the para position to diazonium group of these supports (after diazotization) enhances reactivity in azo coupling. 'Reversed' azo coupling is the reaction of a matrix containing functional groups capable of reacting with diazonium groups of a ligand. Preparation of a suitable matrix and examples of diazotizable ligands are given.
Keywords: Ligands; chromatografie afinitní; Diazonium Compounds; Chromatography, Affinity; ligandy; diazoniové sloučeniny